Research on Control Strategy of Vehicle Rotary Transformer and Permanent Magnet Synchronous Motor Joint Measurement Platform Based on Real-Time Operating System - Xinyu, Sun; Jianping, Yu; Jing, Luo; Kelin, Liu; Yusheng, Fu; Wentao, Tang (2024 International Conference on Electronics and Devices, Computational Science (ICEDCS), 2024)
Aiming at the characteristics of high dynamics and strong interference in vehicle environment, this paper proposes a control strategy of vehicle rotary transformer and permanent magnet synchronous motor joint measurement platform based on real-time operating system. Firstly, the vector control algorithm suitable for vehicle environment is designed. By decoupling current and flux linkage, the high efficiency and high performance of the motor are realized. The control system of the joint measurement platform designed in this paper integrates the real-time monitoring and control functions of the vehicle rotating transformer and permanent magnet synchronous motor. Through the optimized vector control algorithm, the cooperative work of the motor and the rotary transformer is realized. In order to verify the effectiveness of the control strategy, detailed system simulation is carried out, including motor starting, acceleration, deceleration and load changes. The simulation results show that the proposed control strategy can significantly improve the performance of the vehicle-mounted rotary transformer and permanent magnet synchronous motor joint measurement platform. Especially under complex conditions, the system can respond quickly, maintain stable operation, and show good robustness and adaptability. In addition, the simulation results also reveal the dynamic characteristics of the system under different working modes, which provides theoretical basis and data support for the optimization design of the vehicle system.